Digital forensics and cyber crime : first international ICST conference, ICDF2C 2009, Albany, NY, USA, September 30-October 2, 2009 : reevised selected papers - International Conference on Digital Forensics and Cyber Crime 2009 : Albany, N.Y.); Goel, Sanjay (Berlin ; New York : Springer, 2010)
Constitutes the post-conference proceedings of the First International ICST Conference, ICDF2C 2009, held September 30 - October 2, 2009, in Albany, NY, USA. These 16 papers present the whole gamut of multimedia and handheld device forensics, financial crimes, cyber crime investigations, forensics and law, cyber security, and information warfare.
Accounting & fraud. Digital evidence composition in fraud detection / Sriram Raghavan and S.V. Raghavan -- Multimedia & handheld device forensics. iForensics : forensic analysis of instant messaging on smart phones / Mohammad Iftekhar Husain and Ramalingam Sridhar -- A survey of forensic localization and tracking mechanisms in short-range and cellular networks / Saif Al-Kuwari and Stephen D. Wolthusen -- SMIRK : SMS management and information retrieval kit / Ibrahim Baggili, Ashwin Mohan, and Marcus Rogers -- Localization and detection of vector logo image plagiarism / Jong P. Yoon and Zhixiong Chen -- Analysis of Free Download Manager for forensic artefacts / Muhammad Yasin, Muhammad Arif Wahla, and Firdous Kausar -- On the reliability of cell phone camera fingerprint recognition / Martin Steinebach, Mohamed El Ouariachi, Huajian Liu, and Stefan Ketzenbeisser -- Financial crimes. Towards a new data mining-based approach for anti-money laundering in an international investment bank / Nhien-An Le-Khac, Sammer Markos, and Mohand-Tahar Kechadi -- Cyber crime investigations. Analysis of evidence using formal event reconstruction / Joshua James, Pavel Gladyshev, Mohd Taufik Abdullah, and Yuandong Zhu -- Data mining instant messaging communications to perform author identification for cybercrime investigations / Angela Orebaugh and Dr. Jeremy Allnutt -- Digital evidence retrieval and forensic analysis on gambling machine / Pritheega Magalingam, Azizah Abdul Manaf, Rabiah Ahmad, and Zuraimi Yahya -- Forensics & law. Online acquisition of digital forensic evidence / Mark Scanlon and Mohand-Tahar Kechadi -- Criminal defense challenges in computer forensics / Rebecca Mercuri -- Cyber security & information warfare. Detecting and preventing the electronic transmission of illicit images and its network performance / Amin Ibrahim and Miguel Vargas Martin -- A discretionary access control method for preventing data exfiltration (DE) via removable devices / Duane Wilson and Michael K. Lavine -- A host-based approach to BotNet investigation? / Frank Y.W. Law, K.P. Chow, Pierre K.Y. Lai, and Hayson K.S. Tse.
Includes bibliographical references and index.
Print version record.
Keywords: Computer crimes -- Investigation -- Congresses; Computer crimes -- Congresses; Computer networks -- Security measures -- Congresses; Computer networks -- Access control -- Congresses; LAW -- Forensic Science; Informatique; Computer crimes; Computer crimes -- Investigation; Computer networks -- Access control; Computer networks -- Security measures; Electronic books; Conference papers and proceedings